Encapsulated cyst fat necrosis masquerading as cold abscess - Kashyap, Mehak; Gupta, Neelam; Dubey, Vikas; Kaur, Nechal (International Journal of Research in Medical Sciences, 2021)
Encapsulated fat necrosis is a benign, usually asymptomatic and underreported condition. It is believed to be trauma‐related ischemia and necrosis of fat tissue that gradually detaches from its surroundings. Here we reported a case of encapsulated cyst fat necrosis in a 75 years old female following intramuscular injection, who was clinically diagnosed as cold abscess initially.